China’s Vaccine Diplomacy in South Asia: Geopolitical Perspective (Asian Journal of Pharmaceutics (AJP), 2023)
For major nations to increase their geopolitical influence around the world, health diplomacy has remained a crucialcomponent of their foreign policies. Given the outbreak of COVID-19, the inadequate health-care systems, evenof the developed countries, have been exposed. Although China was blamed for the origination of COVID-19,concomitantly, the same nation has utilized the emergency in the global health field to further its geopoliticalhegemonic influence by putting its diplomacy in the area of global health. On April 27, 2021, Wang Yi, the Chineseforeign minister, participated in a video conference together with his colleagues from Sri Lanka, Afghanistan,Bangladesh, Nepal, and Bangladesh. In an effort to coordinate efforts and talk about Chinese aid in the fightagainst COVID-19 in neighboring nations and post-pandemic recovery, a virtual conference was held. Chineseactions in the area since the coronavirus outbreak have emphasized Beijing’s efforts to strengthen its soft power anddiplomacy. The article’s major conclusion is that China increased its global influence by pursuing health diplomacyto the greatest possible extent. It focuses on China’s use of soft power through its diplomatic efforts in global health.It also looks at how India’s own problems have given China more room to operate in the area.